Exploring EFL Learners' Experiences in Self-Directed Learning Through Social Media Application - Rona Nur Azzahra; Lusi Nurhayati; Ari Purnawan (Universitas Islam Negeri Palopo, 2025)
social media is inseparable from the daily lives of everyone, from young to old. At least one social media account is owned by everyone and many even have more than two social media platforms which is especially true for students who are trying to learn English independently outside of class. This study aims to explore how EFL students utilize social media to help them learn English responsibly through self-directed learning. This study uses a qualitative research design with narrative inquiry, and the data collection instruments used are in-depth interviews and documents. Three (3) students from Universitas Negeri Yogyakarta participated in this study through purposive sampling, where they actively use social media and learn English from there through SDL as a journey to develop their respective abilities and needs. Data analysis was conducted through thematic analysis, and the results showed that although social media was initially used for entertainment, it also became a supporting resource in helping individuals learn English according to their respective speeds, interests, and needs. They gain knowledge in terms of vocabulary, phrases, sentences, etc., which broadens their insights, increases their motivation and confidence, and provides them with easy access, space, and a supportive community. However, behind this flexibility, there is also an impact in the form of a lack of structured study, many distractions, inappropriate content, internet limitations causing dependency, and lack of direct feedback. This research highlights the important point that the success of SDL learning through social media greatly depends on students' critical thinking skills, self-control, initiative, and reflectiveness in managing social media throughout the English learning process.